2015
DOI: 10.1016/j.mam.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathophysiology of hepatic glucose production

Abstract: Maintaining blood glucose concentration within a relatively narrow range through periods of fasting or excess nutrient availability is essential to the survival of the organism. This is achieved through an intricate balance between glucose uptake and endogenous glucose production to maintain constant glucose concentrations. The liver plays a major role in maintaining normal whole body glucose levels by regulating the processes of de novo glucose production (gluconeogenesis) and glycogen breakdown (glycogenolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
185
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(198 citation statements)
references
References 118 publications
1
185
0
1
Order By: Relevance
“…Insulin-resistance, impaired glucose tolerance and beta-cell failure as well as gluconeogenesis are the major contributing factors in the development of type-2 diabetes [11]. Additionally, an aberrant regulation of gluconeogenesis lead to excessive hepatic glucose production, which is responsible for hyperglycemia in diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-resistance, impaired glucose tolerance and beta-cell failure as well as gluconeogenesis are the major contributing factors in the development of type-2 diabetes [11]. Additionally, an aberrant regulation of gluconeogenesis lead to excessive hepatic glucose production, which is responsible for hyperglycemia in diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of AMPK induced inhibition of hepatic gluconeogenesis and promotion of glucose uptake is the main focus of T2DM drugs, such as methotrexate, ginsenoside Rg, cocoa flavonoids and metformin (24)(25)(26). Accumulating evidence has proved that activated AMPK phosphorylated CRE-binding protein (CREB)-regulated transcription co-activator 2 (CRTC2) and prevented the transportation of CRTC2 from cytoplasm to the nucleus, ultimately leading to the downregulation of gluconeogenic genes in the liver (27). AMPK also regulates the expression of GLUT4 to participate in the glucose uptake process (28).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pharmacological intervention of the expression of PEPCK and G-6-Pase is regarded as a potential approach for the treatment of metabolic aberrations. In addition, CRTC2-stimulated PGC-1α is a co-activator protein capable of increasing the transcriptional activation of the G-6-Pase and PEPCK promoters by directly interacting with forkhead box O1 and hepatocyte nuclear factor 4α (27,31,32). Knockout or knockdown of PGC-1α in mice led to lower blood glucose levels, reduction of gluconeogenic gene expression and activation of AMPK (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hepatic gluconeogenesis, rather than glycogenolysis, is increased in patients with T2D (2). Hepatic gluconeogenesis is largely controlled through key rate-limiting enzymes in the gluconeogenic pathway, specifically phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase) (4). Therefore, exploring new regulatory factors of gluconeogenic enzymes to inhibit over-activated hepatic gluconeogenesis is a feasible therapeutic strategy to treat T2D.…”
Section: Introductionmentioning
confidence: 99%